Population dynamics of rice planthoppers, Nilaparvata lugens and Sogatella furcifera (Hemiptera, Delphacidae) in Central Vietnam and its effects on their spring migration to China. Issue 3 (6th December 2016) - Hu, G.; Lu, M.-H.; Tuan, H.A.; Liu, W.-C.; Xie, M.-C.; McInerney, C.E.; Zhai, B.-P.
Abstract: Rice planthopper (RPH) populations of Nilaparvata lugens and Sogatella furcifera periodically have erupted across Asia. Predicting RPH population dynamics and identifying their source areas are crucial for the management of these migratory pests in China, but the origins of the migrants to temperate and subtropical regions in China remains unclear. In particular, their early migration to China in March and April have not yet been explored due to a lack of research data available from potential source areas, Central Vietnam and Laos. In this study, we examined the population dynamics and migratory paths of N. lugens and S. furcifera in Vietnam and South China in 2012 and 2013. Trajectory modeling showed that in March and April in 2012 and 2013, RPH emigrated from source areas in Central Vietnam where rice was maturing to the Red River Delta and South China. Early migrants originated from Southern Central Vietnam (14–16°N), but later most were from Northern Central Vietnam (16–19°N). Analysis of meteorological and light-trap data from Hepu in April (1977–2013) using generalized linear models showed that immigration increased with precipitation in Southern Central Vietnam in January, but declined with precipitation in Northern Central Vietnam in January. These results determined that the RPH originate from overwintering areas in Central Vietnam, but not from southernmost areas of Vietnam. Winter precipitation, rather than temperature was the most important factor determining the number of RPH migrants. Based on their similar population dynamics and low population densities in Central Vietnam, we further speculated that RPH migrate to track ephemeral food resources whilst simultaneously avoiding predators. Migrations do not seem to be initiated by interspecific competition, overcrowding or host deterioration. Nevertheless, S. furcifera establishes populations earlier than N. lugens South China, perhaps to compensate for interspecific competition. We provide new information that could assist with forecasting outbreaks and implementing control measures against these migratory pests.